2016
DOI: 10.7708/ijtte.2016.6(2).10
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing Saturation Flow Rate for Lane Groups in an Urban Area

Abstract: This study focused on determining the prevailing Saturation Flow Rate (SFR) for specific lane groups in an urban area: District of Columbia (DC). The lane groups considered were Through (T), shared Through and Right (TR), shared Through and Left (TL), and exclusive Left turn (L) lane groups. These SFR values could then be used to calculate the local base SFR. The study determined the prevailing SFR for these lane groups based on data collected at 81 intersections. The hypothesis that the mean SFRs for all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…(1) Onde: ICP = Índice de Condição do Pavimento; A = valor deduzível, dependente do tipo do defeito (Ti), do grau de severidade (Sj) e da densidade de defeitos (Dij); i = contador para tipos de defeitos; j = contador para graus de severidade; p = número total de placas defeituosas; mi = número de graus de severidade para o tipo de defeito; F (t,q) = uma função de ajustamento para defeitos múltiplos que varia com o valor deduzível somado (t) e o número de deduções (q). O método de avaliação de defeitos no pavimento para determinação do ICP é amplamente utilizado no Brasil e foi aplicado por vários autores em seus estudos (SONCIM; LOPES et al, 2015;ARHIN et al, 2015;KIRBAS;KARASAHIN, 2017). A nível mundial, utiliza-se o Pavement Condition Index (PCI), uma variação muito próxima do índice brasileiro.…”
Section: Revisão Da Literaturaunclassified
See 2 more Smart Citations
“…(1) Onde: ICP = Índice de Condição do Pavimento; A = valor deduzível, dependente do tipo do defeito (Ti), do grau de severidade (Sj) e da densidade de defeitos (Dij); i = contador para tipos de defeitos; j = contador para graus de severidade; p = número total de placas defeituosas; mi = número de graus de severidade para o tipo de defeito; F (t,q) = uma função de ajustamento para defeitos múltiplos que varia com o valor deduzível somado (t) e o número de deduções (q). O método de avaliação de defeitos no pavimento para determinação do ICP é amplamente utilizado no Brasil e foi aplicado por vários autores em seus estudos (SONCIM; LOPES et al, 2015;ARHIN et al, 2015;KIRBAS;KARASAHIN, 2017). A nível mundial, utiliza-se o Pavement Condition Index (PCI), uma variação muito próxima do índice brasileiro.…”
Section: Revisão Da Literaturaunclassified
“…Em todas as análises do modelo, os resultados foram estatisticamente aceitos como significativos, demonstrando ser mais um método que facilita o processo de avaliação da condição do pavimento. Arhin et al (2015) também encontraram uma maneira simplificada de avaliar pavimentos, estimando o valor do PCI a partir dos valores de irregularidade longitudinal (IRI). Isso foi possível por meio de equações estatísticas, utilizando o método de regressão de mínimos quadrados.…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation
“…Rahman et al [9] Dhaka, Bangladesh Yokohama, Japan TH 2006-2091 1636-2093 Mukwaya and Mwesige [10] Kampala, Uganda TH 1470-1774 Hussain [11] Malaysia TH 1945 Hussayin and Shoukry [12] Cairo, Egypt TH 1617 Coeymans and Neely [13] Santiago, Chile TH 1603 Lee and Do [14] South Korea TH 1978 De Andrade [15] Brazil TH 1660 Bester and Meyers [16] South Africa TH and RT 1711-2370 Chand et al [17] India TH and RT 1869-2083 Siddiqui [18] USA LT 1815 Wang and Benekohal [19] USA LT 1828 Arhin et al [20] USA LT 1460 Chen et al [21] Japan LUT 1496 Liu et al [22] USA LUT 1682 Shokry and Tanaka [23] Egypt LUT 1882 Adams and Hummer [24] USA LUT 1500-2300…”
Section: Sourcementioning
confidence: 99%
“…Another study conducted in North Carolina at 20 intersections in Raleigh, Charlotte, and Asheville, revealed that the mean SFR, based on the headway method proposed by HCM, was around 1750 VPHPL for 250,000 or more population and 1497 VPHPL for populations less than 250,000, which are below the default values suggested by HCM [4]. Furthermore, in an SFR study performed by Arhin et al [5,6] for different lane groups at 81 intersections in the urban area of District of Columbia (DC), United States, results showed that the mean SFR that can be used in the future analysis in the DC area was for left only (1460 VPHPL), shared left and through (1566 VPHPL), through only (1559 VPHPL), and shared through and right (1461 VPHPL). This study concluded that the SFR values for all turning movements were statistically alike.…”
Section: Introductionmentioning
confidence: 99%